Daily discrimination and binge eating among lesbians: a pilot study. Issue 1 (3rd April 2017) - Mason, Tyler B.; Lewis, Robin J.; Heron, Kristin E.
ABSTRACT: Cross-sectional research has shown that discrimination is associated with increased negative affect and binge eating among lesbian women. However, the relation between discrimination and binge eating on a daily basis has received limited empirical examination. We posit that discrimination can represent a form of aversive self-awareness such that after experiencing discrimination, individuals may become more conscious of society's negative feelings towards sexual minorities. Participants were recruited through Facebook and LGBT organisations. A sample of 30 lesbian women aged 18–30 who reported binge eating in the past week completed daily measures of discrimination, negative affect, self-awareness and binge eating for 10 days. Hierarchical linear modelling showed that daily discrimination was associated with greater daily negative affect and lowered daily self-awareness. Daily negative affect was associated with reduced self-awareness, which in turn was associated with more binge eating. These results are consistent with escape theory and demonstrate the negative impact that daily discrimination has on binge eating in daily life among lesbian women via negative affect and lowered self-awareness. This pilot study demonstrates the feasibility of using a daily diary approach to examine discrimination as a risk factor for disordered eating behaviour among lesbian women.